Portable Perfusion Phantom Offers Quantitative Dynamic Contrast-Enhanced Magnetic Resonance Imaging for Accurate Prostate Cancer Grade Stratification: A Pilot Study - Kim, Harrison (Acad Radiol, 2020)
RATIONALE AND OBJECTIVES: The study goal was to test whether the improved accuracy in quantitative dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) measurement using a point-of-care portable perfusion phantom (P4) leads to better stratification of prostate cancer grade. MATERIALS AND METHODS: A prospective clinical study was conducted recruiting 44 patients scheduled for multi-parameter MRI (mpMRI) prostate exams. All participants were imaged with the P4 placed under their pelvic regions. Tissue sampling was carried out for 25 patients at 22±18 (mean±SD) days after mpMRI. On histologic examination, a total of 31 lesions were confirmed as prostate cancer. Tumors were classified into low grade (n=14), intermediate grade (n=10), and high grade (n=7). Tumor perfusion was assessed by volume transfer constant, K(trans), before and after P4-based error correction, and the K(trans) of low, intermediate and high-grade tumors were statistically compared. RESULTS: After P4-based error correction, the K(trans) of low, intermediate, and high-grade tumors were 0.109±0.026 min(−1) (95% CI: .0094 to 0.124 min(−1)), 0.163±0.049 min(−1) (95% CI: 0.129 to 0.198 min(−1)) and 0.356±0.156 min(−1) (95% CI: 0.215 to 0.495 min(−1)), respectively, with statistically significant difference among the groups (low vs intermediate: p=0.002; intermediate vs high: p=0.002; low vs high: p<0.001). The sensitivity and specificity of K(trans) value, 0.14 min(−1), to detect the clinically significant prostate cancer were 88% and 93%, respectively, after P4 based error correction, but those before error correction were 88% and 86%, respectively. CONCLUSION: The P4 allows to reduce errors in quantitative DCE-MRI measurement, enhancing accuracy in stratification of prostate cancer grade.